A Rare Case of Rib Fractures During Centrifuge Training. Issue 1 (4th January 2022) - Tu, Min-Yu; Chu, Hsin; Huang, Yi-Jhih; Chiang, Kwo-Tsao; Tong, Pao-Tsung; Lai, Chung-Yu
ABSTRACT: There are several injuries potentially related to high-G exposure, including neck and back pain, spinal fractures, and pneumomediastinum. We present a young military pilot diagnosed with isolated fractures of the right 9th and 10th ribs via X-ray after high-G exposure (maximum G level: 9G). This patient presented with progressive and localized pain in the right anterior chest and flank region. After conservative treatment with rest and pain management, he recovered from the rib fractures and completed all profile challenges in the advanced high-G training program. A review of the annual health examination of the pilot did not show any rib lesions or other related illnesses. He was qualified for flying class II and considered fit for flight training. His medication history was unremarkable, and he did not have a family history of malignancy, osteoporosis, or osteopenia. He also denied having previously experienced trauma of the rib cage or participated in any strenuous military training program or exercise before centrifuge training. The potential explanations for the multiple rib fractures are repetitive stress from the anti-G straining maneuver and anti-G suit compression of the abdominal bladder. To our knowledge, consecutive rib fractures related to high-G exposure have never been documented. This report may increase the awareness of flight surgeons and training units regarding the risk of chest wall injuries during high-G exposure and encourage them to use multiple diagnostic tools to determine the correct diagnosis.